KONFLIK BATIN TOKOH RYUUJI TAKASU PADA ANIME TORADORA! KARYA YUYUKO TAKEMIYA - Ketut Ayu Satyagathita D. Mahiswari Ketut Ayu Satyagathita D. Mahiswari; Made Henra Dwikarmawan Sudipa (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
Abstract This research purpose is to describe and examine the inner conflicts contained in the main character Ryuuji Takasu in the anime Toradora!. This research is descriptive qualitative and use the data source from the anime Toradora!. The data obtained is analyzed using the theory of inner conflict by Sigmund Freud (1923). In this research, the methods and data collection techniques used are using the listening method and the note-taking technique. The methods and data analysis techniques used are descriptive qualitative, the result of the analysis are then described by informal methods, namely descriptions of words in Indonesian that are easy to understand. The result of this research indicates that the main character Ryuuji Takasu experiences an inner conflict which is analyzed by using three structures of inner conflict namely id, ego and superego.